Women's experience of workplace sexual harassment within the police service: A rapid evidence assessment - Brown, Emma (International journal of police science & management, 2025)
The purpose of this work is to provide a systematic overview of sexual harassment (SH) of female police staff in the workplace. Themes that emerge from this review may aid police leaders’ understanding and help them to take a proactive approach to preventing an environment in which SH is tolerated. A rapid evidence assessment was conducted. The Ovid Platform was used to search the PsycINFO database. Searches were conducted in the College of Policing Library, Criminal Justice Database and Sage journals. Studies were included that focused on experiences of, and approaches to, SH in the police. Studies on addressing SH in the general public, or on incidents of SH by police officers towards the general public, were excluded. Six studies were included that explored the prevalence of, approaches to and risk factors for SH of female staff in the police. The most common form of SH is verbal sexual attention. SH remains highly prevalent in the police and is more commonly experienced by officers than support staff. Women respond by acquiescing to SH, or by handling it themselves. Rates of formal action are relatively low, and women often experience repercussions. Women perceive complaints will lead to ostracism and reduced promotion opportunities. There are signs of positive change, however a male-dominated, misogynistic culture persists. This review contributes to a growing understanding of police force SH; the issues raised will aid policymakers in addressing the most prevalent behaviours, repercussions and police culture.